(untitled) (Lapai Journal of Economics, 2023)
The quest to accelerate the pace of development of the economy in a bid to transform Nigeria into the group of developed economies by achieving certain macroeconomic objectives had called for increasing government expenditure in the provisions of public goods for the people and the nation. In view of the role of public expenditures on national progress and prosperity, this study empirically examined the disaggregated impact of the expenditures on economic growth in Nigeria for the period 1986-2021 using ARDL model as a tool for analysis. The important findings from the study suggest that capital and recurrent expenditures on community, social and economic services significantly boost economic growth in both short and long runs but the recurrent expenditure is negatively significant in the short run. Similarly, recurrent expenditure on community, social and economic services is also positively and significantly related with real GDP. Although capital and recurrent expenditures on administration and transfer are found to retard economic growth in the short run; they turn out to significantly enhance national output in the long run. Other findings from the study revealed that capital stock significantly promotes growth whereas labour slows down the growth across both short and long runs. The study recommends that government should lay a solid foundation and provide a workable business ground for individuals and firms. Government should also pay attention to finance growth enhancing spending categories such as infrastructure, research and development, education and health that would enhance human development in the country.